Wage discrimination and female occupational intensity - Lucifora, Claudio [Verfasser]; Reilly, Barry [Verfasser] (My University, 1990)
"The analysis presented in this paper attempts to shed some light, in the context of the Italian labour market, on wage based gender discrimination effects and on the potential impact of gender occupational distribution on wage determination. The results obtained provide some useful insights for Equal Pay legislation and on the efficacy of Comparable Worth (CW) type policies. The wage equation estimates are broadly in line with results obtained elsewhere in the literature. A discrimination effect of nearly 17% results when an exclusively male occupational structure is considered. The gender wage gap showed to decrease as female intensity increases. In terms of the framework used, two competing interpretations have been proposed and their implications discussed. The implication of different policy measures which, in recent years, generated much discussion among scholars and in political arenas have been considered, namely: CW and Affirmative Action (AA) policies. Future research should consider a structural model of discrimination so as to discriminate between competing models and policy options." (author's abstract) ((en)) Anhand einer repräsentativen Stichprobe (Beschäftigte aus 100 Unternehmen) wird die geschlechtsspezifische Lohndiskriminierung in Italien und ihr Zusammenhang mit der Berufsstruktur untersucht. Wichtige Ergebnisse: In Berufen mit geringem Frauenanteil besteht ein Einkommensdiskriminierungs-Effekt von fast 17 Prozent; dieser Effekt ist jedoch umso geringer, je grösser der Anteil der Frauen in der jeweiligen Berufskategorie ist. Die Autoren erörtern auch Schlussfolgerungen für eine Anti-Diskriminierungspolitik. (IAB2)
Lohndiskriminierung und Frauenanteile in einzelnen Berufen
Keywords: G 1.2.2.1 Lohn- & Tarifsysteme; Geschlechtsspezifische Faktoren; Lohnstruktur; Berufsstruktur; Quantitative Angaben